Evidence-based dentistry: Effectual tool in decision-making - Charu Tandon; Pranav Kumar Singh; Indu Singh; Sunil Chandra Verma (Indian Journal of Dental Sciences, 2019)
The goal of evidence-based dentistry (EBD) is to help practitioners provide their patients with optimal care. The practice-related element in EBD is the clinician's integration of the resulting knowledge with clinical expertise, and patient preferences to determine the treatment to be recommended to individual patients. Periodontology has a rich history and a strong passion for science. Evidence-based periodontology is the application of evidence-based health care to periodontology. The substantial and extensive periodontal information base, developed over the years, has provided a rational basis for choosing the best treatment for patients. Various components of evidence-based periodontology include the production of the best available evidence, the critical appraisal and interpretation of the evidence, the communication and discussion of the evidence to individuals seeking care, and the integration of the evidence with clinical skills and patient values. Evidenced-based approach offers a bridge from science to clinical practice.